2019
DOI: 10.1002/ptr.6415
|View full text |Cite
|
Sign up to set email alerts
|

Lapachol is a novel ribosomal protein S6 kinase 2 inhibitor that suppresses growth and induces intrinsic apoptosis in esophageal squamous cell carcinoma cells

Abstract: Lapachol is a 1,4‐naphthoquinone that is isolated from the Bignoniaceae family. It has been reported to exert anti‐inflammatory, antibacterial, and anticancer activities. However, the anticancer activity of lapachol and its molecular mechanisms against esophageal squamous cell carcinoma (ESCC) cells have not been fully investigated. Herein, we report that lapachol is a novel ribosomal protein S6 kinase 2 (RSK2) inhibitor that suppresses growth and induces intrinsic apoptosis in ESCC cells. We found that lapach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…JB6 mouse epithelial cells have been used to investigate the effects exerted by pharmacological compounds upon various signaling cascades, including epidermal growth factor (EGF)‐induced activation of the PI3K and MAPK pathways (Zu et al, 2019). To determine the effects of harmaline on intracellular signaling, serum‐starved JB6 cells were incubated with harmaline prior to treatment with EGF.…”
Section: Resultsmentioning
confidence: 99%
“…JB6 mouse epithelial cells have been used to investigate the effects exerted by pharmacological compounds upon various signaling cascades, including epidermal growth factor (EGF)‐induced activation of the PI3K and MAPK pathways (Zu et al, 2019). To determine the effects of harmaline on intracellular signaling, serum‐starved JB6 cells were incubated with harmaline prior to treatment with EGF.…”
Section: Resultsmentioning
confidence: 99%
“…Human tumor incidence and death have been steadily rising in recent years, and the incidence of esophageal cancer, in particular, remains high. One of the main reasons for tumor recurrence or difficulty in treatment is the weak immunogenicity or lack of expression of tumor antigens, and the body's immune tolerance to the tumor can lead to escape response when the tumor is attacked by the body, resulting in treatment failure [14][15][16][17][18]. Therefore, reducing tumor drug resistance and improving tumor immunogenicity is the key to successful esophageal tumor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the anticancer potential of lapachol and its analogs have been extensively explored ( 15 , 16 ). These studies reported the ability of lapachol to induce mitochondria-mediated cellular apoptosis by activating caspases and PARP ( 17 ). Lapachol analogs also downregulate the expression of the c-Myc, cyclin D1 and cyclin B1, which induce cell cycle arrest in the S and G2/M phases resulting in inhibition of tumor cell proliferation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%